A Feasibility study on Marine Ornamental Fish - De Asis, Cristina G.; Dimayuga, Bernadette C.; Guerrero, Geraldine Grace P.; Hernandez, Christina Rosario A.; Libo-on, Salvacion P.; Pineda, Abigail Concepcion O. (Diliman, Quezon City College of Engineering, 1994)
The feasibility study was done in three phases: market, technical and financial. The main difficulty encountered was the indefinite nature of the supply of the product to be marketed. The ornamental fish industry is not well-documented and research proved to be the most difficult obstacle in the feasibility study. A summary of the different phases are shown: MARKET STUDY-It was found out that there is no gap for marine aquarium fish in the country since local suppliers are able to meet demand as evidenced by the negligible of imports of marine fish for the past decades. If the export market is to be targeted, a higher net profit per fish since tropical marine fish command higher prices abroad. TECHNICAL STUDY-The technical study traced the different processes involved in the trade of marine ornamental fish and delineated the methods used in each process. The fish are caught by hand nets using the barrier net method and packed using the plastic-bag method. Slight variations exist but these are the general practices in trade. The technical study also showed that the possibility of the cooperative undergoing two phases in its implementation. Due to the limited reef area and the inexperience of the newly trained gatherers and handlers, AVMC may first opt to supplement the exporters, then graduate to exporting in a few years. A production plan for the first five years was presented, as well as the take-off point for the export phase. The capacity requirements was also presented. FINANCIAL STUDY-The total project cost was computed for the phase 1 implementation and credit program of several lending institutions were reviewed to determine the appropriate one for the project. The initial capital outlay is than P200,000 and the DTI Tulong sa Tao has a micro-credit program suitable for NGO's or cooperatives. The projected income, cash flow and balance sheet were presented to determine the financial performance of the cooperative.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Ornamental fish trade; Pet industry; Participatory monitoring and evaluation (Project management)